An axi-symmetric thermo-hydraulic model to better understand spot laser welding - Medale, Marc; Touvrey, Charline; Fabbro, Rémy (European Journal of Computational Mechanics, 2008)
The aim of this study is to better understand the basic mechanisms leading to possible defect occurrence in spot laser welding. For that purpose we have developed a numerical model, which takes into account the key-hole dynamics together with a dedicated energy deposition model featuring the multiple reflection effects. Many experiments have also been achieved enabling us to report several defect classes. The analysis of some of these scenarios have been performed and favourably compared to experiments.